Effect of breed on cis-9, trans-11 and trans-10, cis-12 Conjugated Linoleic Acids (CLA) concentrations in milk fat of dairy cattle and the relationship of these CLA with other unsaturated C18 fatty acids - Mohammed Ali, Yassir; Abdul Kadir, Arifah; Yaakub, Halimatun; Ahmad, Zuraini; Zakaria, Zainul Amiruddin; Somchit, Muhammad Nazrul (Universiti Putra Malaysia Press, 2012)
Much attention has been given to unsaturated carbon 18 fatty acids in milk, particularly conjugated linoleicacids (CLAs) which have a beneficial effect on human health. This study was undertaken to investigate theeffect of breed on cis-9, trans-11 and trans-10, cis-12 CLA isomers in the milk fat of dairy cattle and theirrelationship with other unsaturated carbon 18 fatty acids. Mafriwal (n=15) and Jersey (n=15) cows were atmid-lactation period, grazed on pasture and given 5.5kg of concentrate per head daily. The composition ofmilk fatty acid was determined using gas chromatography after the extraction of milk fat using the modifiedFolch's method. The results showed that breed had an effect on cis-9, trans-11 CLA deposition in milk fat.The level of cis-9, trans-11 CLA in milk fat of Mafriwal was significantly higher (P<0.05) than that of theJersey cows, while the levels of trans-10, cis-12 CLA were not significantly different between the two breeds.The levels of cis-9, trans-11 CLA were positively correlated with the concentration of trans 11-octadecenoic(C18:1), cis 9-octadecenoic (C18:1) and octadecatrienoic (C18:3) acids. A positive correlation was also observedbetween the levels of trans-10, cis-12 CLA and octadecatrienoic (C18:3) acid in milk fat. These results indicatedthat breed selection could be used to improve the quality of milk for human consumption.